Big Data Analytics for Large Scale Wireless Body Area Networks; Challenges, and Applications - Abdulshaheed H.R.; Abbas H.H.; Ahmed E.Q.; Al-Barazanchi I. (Springer Science and Business Media Deutschland GmbH, 2023)
Advanced Analytics; Big data; Data Analytics; Wireless sensor networks; Cloud-based; Condition; Development of science and technologies; Human society; Human subjects; Implementation process; Large amounts of data; Large scale wireless body area network; Large-scales; Wireless body area network; Wireless local area networks (WLAN)